Effects of Autonomy Support and Emotion Regulation on Teacher Burnout in the Era of the COVID-19 Pandemic - Chang, Mei-Lin; Gaines, Rachel E.; Mosley, Kristen C. (Frontiers in Psychology, 2022)
The COVID-19 pandemic has exacerbated levels of stress and anxiety for P-12 teachers around the globe. The present study aims to understand teachers’ emotional experiences and feelings of burnout during the pandemic, and how individual (i.e., emotion regulation strategies) or contextual factors (e.g.,, school administrative support) intersect with different facets of their emotional experiences. Using a sequential explanatory mixed methods design, we collected and examined survey and interview data from teachers in the southeastern United States. The structural equation model confirmed the relationships among the following latent variables: negative emotion, emotion regulation, autonomy support, burnout, and teacher enthusiasm. Qualitative findings provide further insight in the contextualized nature of these relationships and how they play out across various schools and districts.